Herbal medicine as an auspicious therapeutic approach for the eradication of Helicobacter pylori infection: A concise review. Issue 10 (7th March 2019) - Ghasemian, Abdolmajid; Fattahi, Azam; Shokouhi Mostafavi, Seyyed Khalil; Almarzoqi, Ali Hussein; Memariani, Mojtaba; Ben Braiek, Olfa; Yassine, Hadi M.; Mostafavi, Neda Sadat Shokouhi; Ahmed, Mohanad Mohsin; Mirforughi, Seyede Amene
Abstract: Helicobacter pylori ( H. pylori ) causes gastric mucosa inflammation and gastric cancer mostly via several virulence factors. Induction of proinflammatory pathways plays a crucial role in chronic inflammation, gastric carcinoma, and H. pylori pathogenesis. Herbal medicines (HMs) are nontoxic, inexpensive, and mostly anti‐inflammatory reminding meticulous emphasis on the elimination of H. pylori and gastric cancer. Several HM has exerted paramount anti‐ H. pylori traits. In addition, they exert anti‐inflammatory effects through several cellular circuits such as inhibition of 5′‐adenosine monophosphate‐activated protein kinase, nuclear factor‐κB, and activator protein‐1 pathway activation leading to the inhibition of proinflammatory cytokines (interleukin 1α [IL‐1α], IL‐1β, IL‐6, IL‐8, IL‐12, interferon γ, and tumor necrosis factor‐α) expression. Furthermore, they inhibit nitrous oxide release and COX‐2 and iNOS activity. The apoptosis induction in Th1 and Th17‐polarized lymphocytes and M2‐macrophagic polarization and STAT6 activation has also been exhibited. Thus, their exact consumable amount has not been revealed, and clinical trials are needed to achieve optimal concentration and their pharmacokinetics. In the aspect of bioavailability, solubility, absorption, and metabolism of herbal compounds, nanocarriers such as poly lactideco‐glycolide‐based loading and related formulations are helpful. Noticeably, combined therapies accompanied by probiotics can also be examined for better clearance of gastric mucosa. In addition, downregulation of inflammatory microRNAs (miRNAs) by HMs and upregulation of those anti‐inflammatory miRNAs is proposed to protect the gastric mucosa. Thus there is anticipation that in near future HM‐based formulations and proper delivery systems are possibly applicable against gastric cancer or other ailments because of H. pylori .